Sensory Integration Ability and Social Adjustment in Elementary School Students - Junilia, Elsy; Dharmawan, Akhmad Kheru (Utan Kayu Publishing, 2023)
This study aimed to determine the relationship between the sensory integration ability with social adjustment in elementary school students. The hypothesis used in this study was there a relationship between sensory integration ability with social adjustment in elementary school students. The subject in this study were 23 student at class IV Ubadah in SDIT X Bandar Lampung. The data of this study is taken by sensory integration and social adjustment scale with data analysis using Pearson product moment correlation analysis. The result showed that there was a significant relationship between sensory integration with social adjustment in elementary school students in SDIT X Bandar Lampung at class IV Ubadah (r=0,676 with p>0,05). The relationship between the two variables is high, the higher the sensory integration ability, the higher social adjustment ability would be. Abstrak: Penelitian ini bertujuan untuk mengetahui hubungan antara kemampuan sensori integrasi dengan penyesuaian sosial pada siswa sekolah dasar. Hipotesis yang digunakan adalah ada hubungan antara kemampuan sensori integrasi dengan penyesuaian sosial pada siswa sekolah dasar. Subyek dalam penelitian ini adalah siswa SDIT X Bandar Lampung kelas IV Ubadah yang berjumlah 23 orang. Data penelitian ini diambil dengan menggunakan skala sensori integrasi dan skala penyesuaian sosial dengan analisis data menggunakan analisis korelasi product moment Pearson. Hasil analisis menunjukan bahwa ada hubungan yang signifikan antara sensori integrasi dengan penyesuaian sosial pada siswa sekolah dasar di SDIT X kelas IV Ubadah (r=0,676 dengan p>0,05). Hubungan kedua variabel adalah tinggi, maka semakin tinggi kemampuan sensori integrasi maka semakin tinggi kemampuan penyesuaian sosial.